Perbandingan Strategi Pemberitaan Bjorka Dalam Media Berita Daring: Analisis Wacana Kritis Dengan Teori Van Leeuwen - Salim, Emir; Dewi, Haru Deliana (Peneliti.net, 2024)
This study discusses the comparison of news strategies related to Bjorka in bilingual news on online news media, namely Tempo.co, Viva.co.id, Liputan6.com, Antaranews.com, and Indonesiawindow.com, which are translated from Indonesian as the source language into English as the target language. This study aims to see whether there are differences in the application of van Leuween's theoretical model of exclusion and inclusion in Indonesian and English news. Van Leuween's theory is used in critical discourse analysis to see how actors are portrayed in the news. This research uses a descriptive qualitative method with a linguistic corpus analysis approach to obtain a parallel corpus, so that the news in both languages can be compared in parallel. The results of this study found exclusion and inclusion strategies in the texts of both languages, as well as some changes in reporting strategies caused by the translation process from Indonesian news to English news.